Islamic Boarding School Strategies for Preventing Underage Marriage: A Study at Nurul Azhar Talawe Islamic Boarding School - Hasdar B Haryanto; Agus Muchsin; M. Ali Rusdi; Rusdaya Basri; Zainal Said (Manunggal Halim Jaya, 2026)
Underage marriage remains a persistent social issue in Indonesia despite the enactment of Law Number 16 of 2019, which raised the minimum legal age of marriage for both men and women to nineteen years. Although legal reform provides stronger protection for children, its effectiveness largely depends on the active participation of educational institutions, particularly Islamic boarding schools (pesantren), in promoting awareness and preventive education. This study aims to analyze the strategies implemented by Nurul Azhar Talawe Islamic Boarding School, Sidenreng Rappang Regency, in preventing underage marriage following the legal reform of marriage age. This study employed a qualitative field research design. Data were collected through in-depth interviews, participant observation, and document analysis involving boarding school leaders, teachers, students, parents, and community leaders selected purposively according to their involvement in educational and marriage-related issues. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while source and method triangulation were employed to ensure credibility and trustworthiness. The findings reveal that the Islamic boarding school implements an integrated prevention strategy consisting of Islamic family education (fiqh munakahat), dissemination of marriage law reform, character education, counseling services, parental engagement, and collaboration with religious and governmental institutions. The effectiveness of these programs is supported by strong institutional commitment, parental involvement, and students' increasing awareness of educational attainment before marriage. Nevertheless, economic hardship, socio-cultural traditions, and peer influence remain major barriers to prevention efforts. The study contributes to the growing literature by demonstrating that Islamic boarding schools function not only as religious educational institutions but also as strategic social agents in child protection and underage marriage prevention through value-based education and community engagement.